Present status of resistance to collar rot disease caused by Sclerotium rolfsii Sacc in soybean: Present status of resistance to collar rot disease caused by Sclerotium rolfsii Sacc in soybean - RAJKUMAR RAMTEKE; VENNAMPALLY NATARAJ; M SHIVAKUMAR; SANJEEV KUMAR; LAXMAN SINGH RAJPUT; SUBHASH CHANDRA; VANGALA RAJESH (Journal of Oilseeds Research, 2020)
Till date, none of the soybean cultivars are reported as immune to Sclerotium blight. A very meagre work has been done on understanding of genetics resistance to S. rolfsii in soybean. Crosses were made between collar rot resistant soybean genotype PK 327 with other agronomically superior parents and the F1 seed was collected. Mapping populations are being developed to identify genes/QTL governing resistance.